La variació sintàctica: uniformitat en la diversitat - Rigau, Gemma (Caplletra. Revista Internacional de Filologia, 1998)
The study of the syntactic variation of the dialects of a language is a good instrument to understand the general properties of language and the syntactic principles that govern the limits of variation in sentence structure. This paper deals with two topics of Catalan sintax, which are given different solutions by the speakers depending on the dialects. One of them is at the interface between syntax and morphology; the other, at the interface between syntax and semantics. The both are related to agreement: morphological features agreement and lexical features agreement. Specifically, we will analise number agreement in deontic sentences with the verb caldre from dialects where this verb is still alive, and we will also comment on the behavior of polariry elements in Rossellonese and North Valencian.